Application of arthroscopic system in the treatment of lactational breast abscess - Longquan Lou; Wei Ma; Xiaojin Liu; Haibin Shen; Haiming Wang; Hao Lv (BMC Surgery, 2022)
Abstract Purpose Optimal treatment of breast abscesses has been controversial. Herein, we report an innovative method for the operative treatment of lactational mammary abscesses. Methods Nineteen lactating patients diagnosed with breast abscesses were enrolled in the study, and abscess debridement and drainage were performed using an arthroscopic system. The clinical characteristics of the patients were recorded to evaluate the feasibility, efficacy, and cosmetic results of arthroscopic surgery for breast abscesses. Results All 19 patients were cured and did not relapse within the 6-month-follow-up period. One patient stopped breastfeeding due to breast leakage. All patients were satisfied with the postoperative appearance of the breast. Conclusion Arthroscopic debridement and drainage are effective treatment methods for lactational breast abscesses, with a high cure rate, few complications, and satisfactory cosmetic outcomes.